Pengembangan Kemampuan Berbicara Bahasa Inggris Melalui Pendampingan Latihan Lapangan Untuk Siswa SMA IT AL-Kamal NW - S, Sutarman (Yayasan Daarul Huda Kruengmane, 2025)
Speaking skills in English are essential competencies that students need to master in order to face global challenges in the modern era. However, in many schools, particularly in semi-urban and rural areas such as SMA IT Al-Kamal NW, students’ speaking ability remains relatively low due to limited English-speaking environments and insufficient speaking practice. To address this issue, a field practice-based mentoring program was implemented in the international tourism environment of Gili Trawangan to enhance students' English-speaking skills. This program was designed with a participatory approach and student-centered learning method, where students actively engage in various speaking activities, such as role play, group discussions, interview simulations, and presentations. The implementation of the program resulted in a significant improvement in students’ speaking skills, particularly in terms of fluency, pronunciation clarity, and confidence. Additionally, students' motivation to learn English increased due to the more contextual and meaningful speaking experiences they encountered. The evaluation of the program was conducted through oral tests, observations, and feedback from students and teachers. This program is expected to serve as a beneficial learning model for other schools facing similar challenges. With continuous support from schools, teachers, students, and the community, the mentoring initiative can make a substantial contribution to improving the quality of education and students’ communication skills in the Lombok region and beyond.